FAITH AND OBEDIENCE MANAGEMENT PROGRAM (Case Study: in SMPN 1 Selong, East Lombok Regency) - Haritani, Hartini -; Sujanto, Bedjo; Akbar, Ma’ruf (Journal of Education Research in Administration and Management (JERAM), 2018)
This research aims to find the strentghs of iman and taqwa program management and the implementation of obedience values towards students’ behavior alteration. This research used qualitative approach with the method of case study. Research design and information were obtained through observation, interview, and analyzing documents. The data was analyzed by comparing the field data and the supporting theories through technique and source triangulation. Research result indicated that the iman and taqwa program management was in accordance with management principles, starting from the planning, organizing, implementing, monitoring, and evaluating. The implementation of iman and taqwa program conducted by the OSIS board and there has been the habituation and internalization of obedience values in students’ daily behavior. Recommendations: first, to the principal, the weaknesses and strengths of the program should be made as the inspection in the program’s management. The weaknesses of the program were in the archiving process, findings of the program were not made as the discussion material for the official planning program. The strength in this program’s management is invoking all school elements, especially OSIS board is so good. Second, to the local government, the findings of this program should be made as the basis in arranging policy, such as facilitate a management training for the principal and the program’s supervisor and the recruitment of prospectrive principal has to have managerial capability.